Biomarkers in Immunotherapy-Based Precision Treatments of Digestive System Tumors - Zeng, Zhu; Yang, Biao; Liao, Zhengyin (Frontiers in Oncology, 2021)
Immunotherapy, represented by immune checkpoint inhibitors (mainly referring to programmed death-1/programmed death-ligand 1 blockades), derives durable remission and survival benefits for multiple tumor types including digestive system tumors (gastric cancer, colorectal cancer and hepatocellular carcinoma), particularly those with metastatic or recurrent lesions. Even so, not all patients would well respond to anti-programmed death-1/programmed death-ligand 1 agents in gastrointestinal malignancies, also suggesting that biomarkers are required to identify the responders and non-responders, as well as to predict the clinical outcomes. And programmed death-ligand 1expression has increasingly emerged as a potential biomarker when predicting the immunotherapy-based efficacy; but regrettably, only through programmed death-ligand 1 alone is insufficient to distinguish patients. Other molecules, such as tumor mutational burden, microsatellite instability, and circulating tumor DNA as well, are involved in further explorations. Overall, there are not yet a perfect biomarker in immunotherapy for digestive system tumors nowadays as a result of the inherent limitations, especially for hepatocellular carcinoma. Standardizing and harmonizing the assessments of existing biomarkers, meanwhile, turning to the other novel biomarkers are presumably wise and feasible.